Gambaran Kepribadian Maya Angelou Dalam Puisi Caged Bird dan Stil I Rise - Mulpah, Sonia Maria (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
The title of this research is Gambaran Kepribadian Maya Angelou Dalam Puisi Caged Bird dan Still I Rise. This research aims to find Maya Angelou's personality in the poems entitled Caged Bird and Still I Rise. This research used personality theory and expressive approach. This research also used qualitative research conducted with descriptive method. The writer found that there are three characteristics of a fully functioning personality in Maya Angelou through her poems, as follows; (1) Openness to experience, (2) Increasingly Existential Living, (3) Trust feelings.